PENGARUH PENGGUNAAN DYE TUNGGAL DAN DYE CAMPURAN ANTOSIANIN-KLOROFIL TERHADAP EFISIENSI KERJA DYE SENSITIZED SOLAR CELL (DSSC) - Manurung, Diana Novita; Nurhidayah; Deswardani, Frastica (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2021)
Research on the performance of Dye Sensitized Solar Cell (DSSC) using single dye, mixture of anthocyanin and chlorophyll has been done. The purpose of this study was to identification influence the type of dye to the working efficiency of DSSC. This research included in experimental research. The working electrode of DSSC was made of dyes from dragon fruit, red spinach, pandanus leaves, cassava leaves and made of TiO2 semiconductor that superimposed with doctor blade method on FTO glass. While the counter electrode was made of 2B pencil carbon-soot a candle flame. Measurements absorbance of each type of dye using spectrophotometer UV-Vis to determine the absorbance values of each type of dye, the highest absorbance at dye mixture from dragon fruit- pandanus leaves. Measurement of currents and voltages using a multimeter with a light source of the sun to determine the efficiency of DSSC, the best efficiency values obtained in DSSC that used dye mixture from dragon fruit-pandanus leaves is equel to 0,002829091% and red spinach-cassava leaves is equel to 0,002222504%. The usage of dye mixture can improve efficiency of DSSC.